Development of an Incinerator with a Multi-Stage Condenser System as an Effort to Reduce CO₂ Emissions Gas from Plastic Waste Burning in Gorontalo City - Raghel Yunginger; Yusuf Usman; Meilan Demulawa; Salmawaty Tansa; Mohamad Jahja; Muhammad Yunus (BULETIN FISIKA, 2026)
The increasing plastic waste volume in Gorontalo City is not balanced by a good management system, making people choose to burn their waste in open space. Not only makes a bad scene, this burning emits dangerous gases such as CO2 that contributes to poor air quality and climate change. This study has developed an environmentally friendly incinerator with a stacked condenser system that emits less CO2 gas. This incinerator consists of three main components: a combustion zone, as the place where plastic waste is burned; a chimney, for the flowing of gas; and stacked condensors, for cooling and keeping the gas before emitting it out. We test the incinerator with and without condensors based on the CO2 emission from 20 minutes' burning of 1.5 kg of plastic waste. The results show that an incinerator with a stacked condensor system can significantly reduce CO2 gas emissions by 18.88% more than an incinerator without condensors. This implies that incinerator with stacked condensors can be an alternative way to reduce CO2 gas from open-space waste burning on a small scale.